Measurement of jet radial profiles in Pb-Pb collisions at √sNN=2.76 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physics letters, 2019)
The jet radial structure and particle transverse momentum (pT) composition within jets are presented in centrality-selected Pb-Pb collisions at sNN=2.76 TeV. Track-based jets, which are also called charged jets, were reconstructed with a resolution parameter of R=0.3 at midrapidity |ηch jet|<0.6 for transverse momenta pT,ch jet=30-120 GeV/c. Jet-hadron correlations in relative azimuth and pseudorapidity space (Δφ,Δη) are measured to study the distribution of the associated particles around the jet axis for different pT,assoc-ranges between 1 and 20 GeV/c. The data in Pb-Pb collisions are compared to reference distributions for pp collisions, obtained using embedded PYTHIA simulations. The number of high-pT associate particles (4<pT,assoc<20 GeV/c) in Pb-Pb collisions is found to be suppressed compared to the reference by 30 to 10%, depending on centrality. The radial particle distribution relative to the jet axis shows a moderate modification in Pb-Pb collisions with respect to PYTHIA. High-pT associate particles are slightly more collimated in Pb-Pb collisions compared to the reference, while low-pT associate particles tend to be broadened. The results, which are presented for the first time down to pT,ch jet=30 GeV/c in Pb-Pb collisions, are compatible with both previous jet-hadron-related measurements from the CMS Collaboration and jet shape measurements from the ALICE Collaboration at higher pT, and add further support for the established picture of in-medium parton energy loss.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und 1002 weitere Personen]
Gesehen am 25.01.2022